Study of the association of pregnancy unique quantification of emesis score with adverse feto-maternal outcomes in pregnancy: a prospective observational cohort study - Nautiyal, Monika; Warman, Shalini; Shanker, Ojasvi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Nausea and vomiting of pregnancy (NVP) affect up to 80% of gestations, ranging from mild discomfort to severe hyperemesis gravidarum. While often dismissed as a benign condition, NVP may be linked to significant adverse feto-maternal outcomes. This prospective study evaluated the clinical utility of the pregnancy-unique quantification of emesis (PUQE-24) scoring system as a prognostic tool for predicting complications among 300 pregnant women at a tertiary care hospital in Eastern India. Methods: This prospective observational study (April 2023–March 2025) categorized 300 first-trimester participants into mild (≤6), moderate (7–12), and severe (13–15) NVP groups using the PUQE-24 scale. Demographic data, clinical markers (ketonuria, liver enzymes), and hospitalization metrics were documented. All participants were followed through delivery to record maternal outcomes (anemia, GDM, and hypertension) and fetal outcomes (birth weight and gestational age). Results: NVP was classified as mild (46.3%), moderate (35.0%), and severe (18.7%). Severe cases showed significant correlations with maternal age ≤30 years. 100% of severe cases required hospitalization (mean 4.4 days) with an 83.9% readmission rate. Severe NVP also demonstrated significantly higher rates of anemia (78.6%), GDM (58.9%), preterm delivery (83.0%), and low birth weight (94.3%) compared to mild cases. Conclusions: The PUQE-24 score is a vital prognostic tool. Strong associations between NVP severity and adverse outcomes like preterm birth and fetal growth restriction necessitate early standardized assessment and targeted intervention, especially in resource-limited settings.